The biblical hero : portraits in nobility and fallibility - Rabin, Elliott (University of Nebraska Press, 2020)
"Approaching the Bible in an original way-comparing biblical heroes to heroes in world literature-Elliott Rabin addresses core biblical questions: What is the Bible telling us about what it means to be a hero? Why do we need such heroes, possibly now more than ever?"--